COVID-19 orthodontic practice management guidelines version 1.0 by Malaysian Association of Orthodontists - Othman, Siti Adibah; Kereshanan, Shalene; Chek, Wey Mang; Awang Abdullah, Asma Alhusna; Abu Bakar, Noraini; Bahar, Aufa Dahlia; Nik Mustafa, Nik Mukhriz; Othman, Yatimah; Yong, Wong Tuck (Malaysian Association of Orthodontists (MAO), 2020)
Most parts of the world are seeing cases of COVID-19 outbreaks. The 2019 pandemic of novel coronavirus, SARS CoV-2, has expanded from its original centre - Wuhan, China to a growing number of countries worldwide including our nation Malaysia. Although authorities in China and some other countries have succeeded in slowing their outbreaks, the situation remains unpredictable, laced with many uncertainties. As of 5th June 2020, the WHO reports that there are over 6.7 million cases worldwide and tragically over 393,000 reported deaths. The effects of this COVID-19 are numerous and unprecedented. This global pandemic has harshly affected the day-to-day running of world. Dentistry, including orthodontic clinical practice has been brought to a screeching halt when our Malaysian government imposed the Movement Restricted Order as of 18th March 2020. As efforts to combat the viral transmission have been by and large successful in managing to “flatten the curve” of infectivity for this highly infectious virus, various guidelines have been put together to ensure resumption of clinical practice in a safe manner for much needed continuation of patient care. This particular guideline aims to provide some guidance and advice from the Malaysian Association of Orthodontists specifically tailored for orthodontic patient care within the Malaysian context during this transitional phase, until such a time when vaccine or definitive therapy is successfully developed. This approach, shall be used in addition to the existing universal cross-infection protocols available (Malaysian Dental Council Guidelines for Infection Control in Dental Practice 2017 and recommendations by the Ministry of Health Malaysia) and regulations by the Government of Malaysia from time to time as we improve our knowledge and experience in dealing with this COVID-19. Orthodontic practices will need some time for acclimatisation but it is highly recommended that these become ‘new-normal’ practices in the near future with the main aim to protect all our patients, colleagues, staff and the public against the spread of this viral pandemic.